Medicinal Plant Sector in India: Status and Sustainability - Singh, Sukhjinder; Kumar, Sanjay (International Journal of Economic Plants, 2021)
Medicinal systems in India emerged during Indus Valley civilization. In Indian herbal texts use of herbal medicines has been mentioned. Total global market of herbal products is estimated at $ 85 billion. Asian continent occupies about 30% of the market share in the global herbal market. European countries act as biggest importers of herbal health products. In India, there are 6 major, 21 medium and 37 minor herbal markets. Due to this increasing demand for medicinal plants, some of the medicinal plants have become extinct. To have the sustainability of medicinal plants, both in-situ and ex-situ conservation methodology along with some policy measures like certification of medicinal plant produce, contract farming of medicinal plants etc. is needed to promote farming of medicinal plants.